Documenting genomics: Applying archival theory to preserving the records of the Human Genome Project. (February 2016) - Shaw, Jennifer
Abstract: The Human Genome Archive Project (HGAP) aimed to preserve the documentary heritage of the UK's contribution to the Human Genome Project (HGP) by using archival theory to develop a suitable methodology for capturing the results of modern, collaborative science. After assessing past projects and different archival theories, the HGAP used an approach based on the theory of documentation strategy to try to capture the records of a scientific project that had an influence beyond the purely scientific sphere. The HGAP was an archival survey that ran for two years. It led to ninety scientists being contacted and has, so far, led to six collections being deposited in the Wellcome Library, with additional collections being deposited in other UK repositories. In applying documentation strategy the HGAP was attempting to move away from traditional archival approaches to science, which have generally focused on retired Nobel Prize winners. It has been partially successful in this aim, having managed to secure collections from people who are not 'big names', but who made an important contribution to the HGP. However, the attempt to redress the gender imbalance in scientific collections and to improve record-keeping in scientific organisations has continued to be difficult to achieve. Highlights: The Human Genome Archive Project aimed to preserve scientific records. Previous approaches to scientific collecting were not suitable for big science. Archival theories were assessed before documentation strategy was chosen. The project has led to new collections being deposited in UK archives. Problems still remain with scientific record-keeping.